Leadership and Gender Factors in Women’s Political Participation in Malaysia (1980-2013) - Nor Rafidah, Saidon; Sity, Daud; Mohd, Samsudin (Universiti Kebangsaan Malaysia, 2017)
Women today are important asset to the society and country. They are not only capable of leading the states, but are also able to lead the country; the participation of women in administrative bodies at national and local levels could bring changes to policies and laws that focus on women, children and families. However, women are still lagging behind men in political leadership, especially in Malaysia. This study relates leadership and gender factors in political participation of women in Malaysia in 1980-2013. The aim of this study was to examine the factors of leadership and gender in women's political participation. The research method used was a qualitative method through observation and interviews with some respondents selected among former cabinet ministers, scholars who have researched on gender and also a member of parliament. In addition, the researchers also obtained secondary data related to this study. The data and tables obtained from reliable sources were then analyzed qualitatively. The conceptual framework used in this study was the leadership theory supported by the concept of gender. The study found that Malaysian women today are better prepared and have a high political awareness and their role as a counterweight in decision making. Therefore, the participation of women in politics is important because it can change the future and society's view of women and their role in decision-making.